2018
DOI: 10.3389/fnagi.2018.00285
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effects of Homotaurine in Patients With Amnestic Mild Cognitive Impairment

Abstract: Alzheimer’s disease (AD) is a fatal dementing neurodegenerative disease, currently lacking an efficacious disease-modifying therapy. In the last years, there has been some interest in the use of homotaurine as a potential therapeutic compound for AD, but more work is still needed to prove its efficacy as disease modifier in dementia. Since inflammation is believed to play a key role in AD development, we sought to investigate here the in vivo homotaurine effect on inflammatory response in patients at the earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
4
16
0
Order By: Relevance
“…Homotaurine is a potential therapeutic compound for AD, as it has anti-inflammatory properties. After taking homotaurine, patients carrying the APOEε4 allele demonstrated a significant decrease in the level of IL-18 (but not other cytokines) [239].…”
Section: And Alzheimer's Diseasementioning
confidence: 93%
“…Homotaurine is a potential therapeutic compound for AD, as it has anti-inflammatory properties. After taking homotaurine, patients carrying the APOEε4 allele demonstrated a significant decrease in the level of IL-18 (but not other cytokines) [239].…”
Section: And Alzheimer's Diseasementioning
confidence: 93%
“…Mechanisms of action of tramiprosate include effects on amyloid, but also anti-inflammatory effects as demonstrated in MCI patients ( 32 , 33 ). A third mechanism of action is linked to the GABA-A receptor (GABA-AR).…”
Section: Tramiprosatementioning
confidence: 99%
“…In this line, a recent study evaluating tramiprosate administration in aMCI patients also showed improved short-term episodic memory performance in ApoE4/4 carriers. In addition to neuropsychological and functional assessments, cytokine levels were performed at baseline and after 1 year, and a significant decrease in IL-18 serum levels was observed, suggesting a drug-related anti-inflammatory effect ( 32 ). Another study in patients with symptomatic MCI showed an even earlier response.…”
Section: Clinical Studies With Tramiprosate In Ad and Other Neurocognmentioning
confidence: 99%
“…Recently APOE ɛ 4 has emerged as a promising therapeutic target for treatment of AD as it plays key role in triggering the disease [ 107 ]. Studies suggest that AD progression can be avoided by targeting APOE ɛ 4 gene and gene products as well as its functions with the aid of the above mentioned approaches [ 108 ]. Immunomodulation with ApoE4 monoclonal antibodies, mimesis through peptides of ApoE and ApoE4 degradation may be helpful as a promising approach for delaying the onset of disease.…”
Section: Discussionmentioning
confidence: 99%